Маніфест української фольклористики - Кирчів, Р. (Народна творчість та етнографія, 2006)
The author deeply researches M. Martynovych's folklore collection on the Ukrainian folk songs "Malorosijskrie pyesni". The given edition, called Manifesto by Mykhajlo Grushevsky, touches the whole complex of the problems on the Ukrainian studies, but first of all it is an outstanding folklore phenomenon. It became the result of the previous interest in folklore, and folk songs in particular; and at the same time it turned out to be a new level of the discourse. The article suggests cultural and historic interpretation of the given collection.